VD_FINDINFO ML / 2025 / 129 vom 26. November 2025 - VD Tribunal cantonal (2025)
MAINLEVÉE DÉFINITIVE, DÉCISION ÉTRANGÈRE, RECONNAISSANCE DE LA DÉCISION | 81 al. 1 LP, 81 al. 3 LP, 33 CL (2007), 38 par. 1 CL (2007)